Strategi Pengelolaan dan Pengembangan pada Tadika Al-Fikh Orchard HQ Malaysia - Thufail, Muhammad Daffa; Hayati, Isra (MODELING: Jurnal Program Studi PGMI, 2025)
Penelitian ini bertujuan untuk tidak hanya memperjelas strategi pengelolaan dan pengembangan usaha pada Tadika Al-Fikh Orchard HQ Malaysia tetapi juga tantangan yang dihadapi dalam implementasi strategi pengelolaan dan pengembangan usaha pada Tadika Al-Fikh Orchard HQ Malaysia. Metode penelitian deskriptif dengan pendekatan kualitatif filsafat postpositivisme. Objek penelitian bertempat di Tadika Al-Fikh Orchard HQ Malaysia. Data primer dan data sekunder penelitian diperoleh tidak hanya dari wawancara dan observasi dengan informan tetapi juga dari kajian pustaka, seperti jurnal, dan buku referensi. Hasil penelitian sebagai berikut: (1) Strategi pengelolaan dan pengembangan usaha pada Tadika Al-Fikh Orchard HQ Malaysia perlu ditambahkan mengingat Tadika Al-Fikh Orchard HQ adalah terwaralaba dalam bidang pendidikan (franchisee). Hal ini menunjukkan pentingnya strategi pengelolaan dan pengembangan usaha. Ketentuan ini mencerminkan pentingnya tanggungjawab dan kewajiban dalam praktik etika bisnis syariah bukan saja dalam pengelolaan, melainkan juga dalam pengembangan usaha; (2) Tantangan yang dihadapi dalam implementasi strategi pengelolaan dan pengembangan usaha pada Tadika Al-Fikh Orchard HQ Malaysia telah teratasi dalam analisis SWOT dan SOP. Setidaknya, dengan pemahaman yang baik tentang aspek-aspek etika bisnis Islam, diharapkan Tadika Al-Fikh Orchard HQ dapat mengelola keuangan mereka secara efektif untuk meningkatkan keberlangsungan usaha Tadika Al-Fikh Orchard HQ di seluruh negara Malaysia. Abstract This research aims to not only clarify the management and business development strategy at Tadika Al-Fikh Orchard HQ Malaysia but also the challenges faced in the implementation of the management and business development strategy at Tadika Al-Fikh Orchard HQ Malaysia. Descriptive research method with a qualitative approach to postpositivism philosophy. The object of the research was located at Tadika Al-Fikh Orchard HQ Malaysia. Primary data and secondary data of research were obtained not only from interviews and observations with informants but also from literature reviews, such as journals, and reference books. The results of this research are as follows: (1) The management and business development strategy at Tadika Al-Fikh Orchard HQ Malaysia needs to be added considering that Tadika Al-Fikh Orchard HQ is a franchisee in the field of education (franchisee). This shows the importance of business management and development strategies. This provision reflects the importance of responsibilities and obligations in the practice of sharia business ethics not only in management, but also in business development; (2) The challenges faced in the implementation of business management and development strategies at Tadika Al-Fikh Orchard HQ Malaysia have been overcome in SWOT analysis and SOP. At least, with a good understanding of the aspects of Islamic business ethics, it is hoped that Tadika Al-Fikh Orchard HQ can manage their finances effectively to improve the sustainability of Tadika Al-Fikh Orchard HQ's business throughout Malaysia.